Suicide attempt and its determinants among youth in central, north, and west Gondar zones, northwest Ethiopia: Findings from the youth health project - Geremew, Alehegn Bishaw; Gelagay, Abebaw Addis; Yeshitila, Hedija Yenus; Azale, Telake; Habitu, Yohannes Aynaw; Abebe, Solomon Mekonnen; Birru, Eshetie Melese; Fentie, Elsa Awoke (Frontiers in Psychiatry, 2023)
Introduction: Suicide is the act of intentionally causing one’s death. Adolescent and youth suicidal behavior, which is an important public health problem worldwide, is a neglected public health issue, especially in middle- and low-income countries including Ethiopia. Therefore, the study aimed to assess the prevalence of suicidal attempt and their determinants among schooling and out-school youth in central, north, and west Gondar zone, Ethiopia. Methods: A community-based cross-sectional study was conducted from March 15 to April 15, 2019, among youth in the central, north, and west Gondar zone. The data of this research was extracted from data collected for the assessment of common health problems and risky behaviors among youth. The data was collected using face-to-face interviewer-administered questionnaires using a multistage cluster sampling procedure. Firstly, a bivariable logistic regression analysis was done and eligible variables were entered into a multivariable logistic regression analysis to identify independent determinants. Adjusted odds ratio with 95%confidence interval was used to identify statistical association and the direction of the association. Results: A total of 1597 youth participated in this study and the mean age of the participants was 19.1±2.8SD. The lifetime prevalence of suicidal attempts in the study participants was 5.5% (95% CI: 4.4%, 6.8%). risky sexual practice (AOR =1.89, 95%CI: 1.19-2.99), The presence of a common mental health problem (AOR = 6.31, 95% CI: 3.78-10.88), personal income (AOR=1.68, 95% CI: 1.05-2.71) and history of violence (AOR=2.81, 95% CI 1.76-4.49) significantly associated with suicidal attempt. Conclusion: In this study, the prevalence of lifetime suicide attempts among youth is found low. The presence of common mental health problems, personal income, risky sexual practices, and a history of violence increases the likelihood of suicidal attempts. Working on the reduction of risky sexual practices, ensuring integration of psychological treatment into violence medical treatment programs, psychosocial support for young people, and integrating with youth-friendly health services to promote mental health would help to reduce suicide attempts among youth